The impact of CSF venous fistula embolization on patient’s quality of life, a longitudinal clinical-radiological exploration - Malo Goapper; Liesjet E.H. van Dokkum; Vincent Costalat; Gaetano Risi; Lucas Corti; Olivia Portalier; Nicolas Lonjon; Emmanuelle Le Bars; Anne Ducros; Federico Cagnazzo (The Journal of Headache and Pain)
Abstract Background Transvenous Onyx embolization of cerebrospinal fluid-venous fistulas (CSFVF) is an emerging and effective treatment for symptomatic spontaneous intracranial hypotension (SIH). This condition significantly impacts patients’ quality of life (QoL) through a variety of debilitating symptoms. Methods Patients were selected from a prospective database of individuals with CSFVF who underwent transvenous Onyx embolization. All participants were asked to complete 13 questionnaires assessing their QoL, before and three months after treatment. Clinical and radiological data were retrospectively collected from the database, and the impact of embolization was evaluated across multiple variables. Correlations and stepwise regression analyses were used to explore relationships between QoL and specific domains including headache, audio-vestibular and psychological symptoms, and spiritual well-being. Results The study included 30 patients (mean age: 60.4 ± 14.1; female-to-male ratio: 2:1) diagnosed with SIH and CSFVF, that were treated successfully with Onyx embolization. There was no treatment-related morbidity. All 28 patients with headache reported symptom improvement, with 64% achieving complete resolution. The response rate was 100% for VAS-QoL, HIT-6, MIDAS grade, VAS-HI, and monthly headache days; lower rates were observed for SF-36 (56.6%), MSQ (96.7%), DHI and THI (90%), and psychological questionnaires (80–90%). Global QoL scores (VAS-QoL: p < 0.001, SF-36: p < 0.05) and QoL scores related to headache significantly improved post-treatment (HIT-6: p = 0.0119; MSQ: p = 0.0004; MIDAS: p = 0.0236). Psychological symptoms like depression and anxiety significantly decreased, while suicidal ideation resolved when present. Significant audio-vestibular QoL improvements were noted for dizziness (p = 0.002) and hearing disturbances (p = 0.021), but not for tinnitus (p = 0.101). MRI findings showed a significant reduction in SIH-related brain abnormalities (mean Bern-score: 6.3 ± 1.9 to 1.7 ± 1.5 post-treatment). However, changes in overall Bern-scores did not correlate with clinical variables, although brain sagging showed a trend toward correlation with headache intensity reduction (r = 0.37, p = 0.06). Conclusion CSFVF embolization is associated with significant radiological and clinical improvements, leading to enhanced global quality of life for patients with SIH.